The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/ejp.1273
|View full text |Cite
|
Sign up to set email alerts
|

The role of psychological flexibility in relation to suicidal thinking in chronic pain

Abstract: This study provides evidence that components of psychological flexibility are associated with a reduced frequency of suicidal thinking in people with chronic pain. Treatments targeting psychological flexibility may help mitigate the impact of chronic pain on suicidal thinking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 38 publications
2
15
0
Order By: Relevance
“…Psychosocial models of chronic pain, such as the Fear-Avoidance Model 20 , have said little to nothing on the topic of suicide, although recently the Psychological Flexibility model of chronic pain 21 has been specifically applied to the context of suicide in this population 22 . The three predominant, "ideation-toaction" psychological models of suicide, the Interpersonal Psychological Theory 13,14 , the Integrated Motivational-Volitional model 15,16 and the Three Step Theory 17 , have also been relatively silent on the topic of chronic pain.…”
Section: Suicide and Chronic Pain: The Theoretical Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychosocial models of chronic pain, such as the Fear-Avoidance Model 20 , have said little to nothing on the topic of suicide, although recently the Psychological Flexibility model of chronic pain 21 has been specifically applied to the context of suicide in this population 22 . The three predominant, "ideation-toaction" psychological models of suicide, the Interpersonal Psychological Theory 13,14 , the Integrated Motivational-Volitional model 15,16 and the Three Step Theory 17 , have also been relatively silent on the topic of chronic pain.…”
Section: Suicide and Chronic Pain: The Theoretical Contextmentioning
confidence: 99%
“…Recently the first study was conducted to directly investigate the role of psychological flexibility in the suicidal ideation -chronic pain relationship 22 . This study suggested that in multivariable analysis acceptance and committed action (a willingness to be with unwanted experiences such as pain and the capacity to continue to act in accordance with valued life goals, even in their presence) remained significantly associated with suicidal ideation even when controlling for depression, pain interferences and presence of widespread pain.…”
Section: Psychological Flexibilitymentioning
confidence: 99%
“…Statistically however, suicidal ideation was only weakly correlated with stress but not with PTS. We suppose that the very low prevalence of suicidal ideation in our sample (6.9%), as compared to 40%–45% in non‐athletic samples with chronic pain (Legarreta et al, ; McCracken et al, ), may be responsible for the negative findings. As athletic participation was reported to be associated with a reduced risk for suicidality (Sabo et al, ) larger sample sizes might be needed.…”
Section: Discussionmentioning
confidence: 56%
“…Recent reviews reported an association between pain and suicidality, both for patients with chronic and acute pain (Fishbain, Lewis, & Gao, 2014;Tang & Crane, 2006), indicating suicidality to be an important issue in athletes with pain. Suicidal ideation in chronic pain is associated with different psychological measures, such as pain-related catastrophizing or helplessness (Breivik et al, 2014;Legarreta et al, 2018;Racine et al, 2014) and is negatively correlated with acceptance and committed action (McCracken et al, 2018), two important aspects of the concept of psychological flexibility (Hayes, Luoma, Bond, Masuda, & Lillis, 2006;McCracken & Morley, 2014). McCracken et al (2018) proposed the model of psychological flexibility as an overarching theoretical approach to comprise these different factors as precursors of suicidality in terms of avoidance of negative experiences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation